2020
DOI: 10.1038/s41396-020-0731-2
|View full text |Cite
|
Sign up to set email alerts
|

Lichen-like association of Chlamydomonas reinhardtii and Aspergillus nidulans protects algal cells from bacteria

Abstract: Organismal interactions within microbial consortia and their responses to harmful intruders remain largely understudied. An important step toward the goal of understanding functional ecological interactions and their evolutionary selection is the study of increasingly complex microbial interaction systems. Here, we discovered a tripartite biosystem consisting of the fungus Aspergillus nidulans, the unicellular green alga Chlamydomonas reinhardtii, and the algicidal bacterium Streptomyces iranensis. Genetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 68 publications
0
50
0
1
Order By: Relevance
“…Given extant lichens, one could specify the fungal component as a member of the kingdom Fungi, but what would a theoretical association involving a member of the Oomycota then constitute and how could one exclude that associations with other fungal-like organisms might exist or might have existed in the past? Associations with photosynthetic algae have also been formed by fungal-like bacteria (Actinomycetes) and by fungi otherwise not forming lichens, such as in the genus Aspergillus, under laboratory conditions (Lazo 1966;Lawrey 1984;Zvyagintsev et al 2010;Lücking and Nelsen 2018;Krespach et al 2020). Since photobionts of lichens represent two domains (including Bacteria) and three kingdoms, there would be no logical reason to restrict mycobionts to a single domain (excluding Bacteria) and kingdom.…”
Section: What Are Lichens and How Should They Be Named?mentioning
confidence: 99%
“…Given extant lichens, one could specify the fungal component as a member of the kingdom Fungi, but what would a theoretical association involving a member of the Oomycota then constitute and how could one exclude that associations with other fungal-like organisms might exist or might have existed in the past? Associations with photosynthetic algae have also been formed by fungal-like bacteria (Actinomycetes) and by fungi otherwise not forming lichens, such as in the genus Aspergillus, under laboratory conditions (Lazo 1966;Lawrey 1984;Zvyagintsev et al 2010;Lücking and Nelsen 2018;Krespach et al 2020). Since photobionts of lichens represent two domains (including Bacteria) and three kingdoms, there would be no logical reason to restrict mycobionts to a single domain (excluding Bacteria) and kingdom.…”
Section: What Are Lichens and How Should They Be Named?mentioning
confidence: 99%
“…In this specific association, the two species were forced, under specific conditions, to mutually support each other's growth. In a very recent study, during the tripartite interaction between C. reinhardtii, Aspergillus nidulans and Streptomyces iranensis, the fungal species was demonstrated to physically defend the microalgae from bacterial algicide compound azalomycin F by forming a protective lipid coat as observed by microscopy [79].…”
Section: Discussionmentioning
confidence: 99%
“…However, C. reinhardtii can also be prone to be attacked by antagonistic bacteria. For example, the soil bacterium Streptomyces iranensis releases the algicide azalomycin F, which is toxic for C. reinhardtii unless the alga protects itself among the mycelia of the fungus Aspergillus nidulans (15). In a previous study, we showed that another soil bacterium, Pseudomonas protegens Pf-5, known to produce a wide variety of secondary metabolites (16), can inhibit the growth of C. reinhardtii (17).…”
Section: Introductionmentioning
confidence: 99%